Aligning diagnostics to the point-of-care: lessons for innovators, evaluators and decision-makers from tuberculosis and HIV. Issue 11 (18th November 2020) - Engel, Nora; Wolffs, Petra F G
Abstract : Diagnostics, including those that work at point-of-care, are an essential part of successful public health responses to infectious diseases and pandemics. Yet, they are not always used or fit intended use settings. This paper reports on key insights from a qualitative study on how those engaged with developing and implementing new point-of-care (POC) diagnostics for tuberculosis (TB) and HIV ensure these technologies work at POC. Ethnographic fieldwork between 2015 and 2017 consisting of 53 semistructured interviews with global stakeholders and visits to workshops, companies, and conferences was combined with 15 semistructured interviews with stakeholders in India including providers, decision-makers, scientists and developers and visits to companies, clinics and laboratories. Our results show how developers and implementer of HIV and TB POC diagnostics aim to know and align their diagnostics to elements in more settings than just intended use, but also the setting of the developer, the global intermediaries, the bug/disease and the competitor. Actors and elements across these five settings define what a good diagnostic is, yet their needs might conflict or change and they are difficult to access. Aligning diagnostics to the POC requires continuous needs assessment throughout development and implementation phases as well as substantive, ongoing investment in relationships with users. The flexibility required for such continuous realigning and iteration clashes with established evaluation procedures and business models in global health and risks favouring certain products over others. The paper concludes with suggestions to strengthen this alignment work and applies this framework to research needs in the wake of COVID-19.